2017
DOI: 10.1590/1983-21252017v30n229rc
|View full text |Cite
|
Sign up to set email alerts
|

REACTION OF SUGARCANE GENOTYPES TO PARASITISM OF Meloidogyne javanica AND Pratylenchus zeae

Abstract: -The objective of this work was to evaluate the response of sugarcane genotypes to Meloidogyne javanica and Pratylenchus zeae. Sugarcane seedlings of the genotypes RB985944, RB987932, RB877935, RB855156, RB935744, RB996961, RB925345, RB935581 and RB966928 obtained from tissue cultures and maintained in pots with sterilized soil in a greenhouse were inoculated with 5,000 eggs + secondstage juveniles of M. javanica or 1,600 of P. zeae per plant, using six replicates per treatment. Tomato (Rutgers) and sorghum (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
7
Order By: Relevance
“…The growing search for less polluting and renewable fuels has turned the sugarcane market into one of the world's most promising in agribusinesses, favoring the expansion of the sugarcane industry. However, despite the Brazilian tradition in sugarcane production, sugarcane productivity is regulated by several factors, with health problems reducing crop productivity in different producing regions, especially those caused by nematodes (BELLÉ et al, 2017;PORTO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing search for less polluting and renewable fuels has turned the sugarcane market into one of the world's most promising in agribusinesses, favoring the expansion of the sugarcane industry. However, despite the Brazilian tradition in sugarcane production, sugarcane productivity is regulated by several factors, with health problems reducing crop productivity in different producing regions, especially those caused by nematodes (BELLÉ et al, 2017;PORTO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The damage caused by nematodes varies according to the population level, soil type, and crop variety (SILVA et al, 2016;BELLÉ et al, 2017;NORONHA et al, 2017;MARANHÃO et al, 2018). When at a high population density, nematodes cause severe damage to the root system, which becomes underdeveloped and inefficient, leading to decreased productivities (SILVA et al, 2017;PORTO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brida et al (2017) explain that the nematode P. brachyurus can penetrate and grow in roots regardless of the soybean cultivar analyzed. Matsuo et al (2012) and Bellé et al (2017) found differences between soybean and sugarcane genotypes, respectively, and classified them as resistant and moderately resistant to Heterodera glycines, Meloidogyne javanica, and Pratylenchus zeae, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…de solo e variedade da cultura (SILVA et al, 2016;BELLÉ et al, 2017;NORONHA et al, 2017;MARANHÃO et al, 2018). Quando em alta densidade populacional, os nematoides causam graves danos ao sistema radicular, que se torna subdesenvolvido e ineficiente, levando à diminuição das produtividades (SILVA et al, 2017;PORTO et al,2018).…”
Section: Introductionunclassified